Perpetual contact : (Cambridge University Press, 2002)
Mobile phones affect every aspect of our personal and professional lives. They have transformed social practices and changed the way we do business, yet surprisingly little serious academic work has been done on them. This book studies the impact of the mobile phone on contemporary society from a social scientific perspective. Providing a comprehensive overview of mobile phones and social interaction, it comprises an introduction covering the key issues, a series of unique national studies and a final section examining specific issues.